Aggregated Compensation Peer Group Disclosure and Managerial Labor Market Competition: A Network Analysis - GAO, RAY RUI; LU, YIFEI (Journal of Accounting Research, 2026)
ABSTRACT In this paper, we develop novel measures of managerial labor market classification and competition by constructing networks of compensation benchmarking peers disclosed in proxy statements. These networks represent firms’ relative positions within the managerial labor market. Our classifications strongly predict executive moves across firms, outperforming a comprehensive set of predictors in the literature. Subsequent tests further demonstrate the strength of our methodology in capturing the multidimensional and dynamic features of the managerial labor market. We also validate our competition measures by showing that they are associated with retention tools, such as higher equity pay and longer pay duration. Finally, we apply our measures to test two theoretical predictions. First, we find that labor market competition could explain controversial pay practices. Second, we demonstrate that the labor market provides managers with tournament incentives to deliver superior future performance.